A small cell bronchogenic carcinoma associated with tumoral hypophosphataemia and inappropriate antidiuresis. Issue 828 (October 1994) - Robin, N.; Gill, G.; van Heyningen, C.; Fraser, W.
Abstract : A patient is described with small cell carcinoma of the lung, associated with profound hypophosphataemia and hyponatraemia. Increased phosphate excretion and inappropriately high urine osmolality were observed. The abnormalities are consistent with tumoral hypophosphataemia and inappropriate antidiuresis. These tumour-related metabolic abnormalities have only been described once before with this malignancy.